Analysis of the toxicity induced by carboplatin and paclitaxel regimen in ovarian cancer patients - Thaís A. GOUVÊA; Gabriela V. CHAVES; Mario J. SOBREIRA- (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2022)
Objective: to analyze of the toxicities induced by carboplatin and paclitaxel regimen in ovarian cancer patients, seeking to identify possible risk factors related to its occurrence and clinical interventions. Method: a retrospective cohort study was conducted involving ovarian cancer patients, enrolled between 2015 and 2017 in a reference oncology hospital in Brazil. They were collected from medical records and prescriptions: demographic, clinical, and pharmacotherapeutic data; information on toxicities induced by treatment; and clinical interventions (chemotherapy dose reduction, chemotherapy suspension, and change of treatment regimen). Drugs were classified according to the Anatomical Therapeutic Chemical (ATC) code. The toxicities were classified as to their severity according to the Common Terminology Criteria for Adverse Events. A descriptive analysis of the variables was performed, the relative risk was calculated, and Fischer's exact test was used to check for possible associated risk factors. A value of p < 0.05 was assumed as statistical significance. Results: the study included 105 patients. Of these, 47% had some comorbidity, 71% were polymedicated, 2% were exposed to drug interactions with the regimen studied, 73% had toxicities, 35% of which were grade > 2. Alopecia and asthenia were the most severe toxicities, and 55% had at least one of the clinical interventions studied, which resulted in a worse prognosis. Women under the age of 60 had a higher risk of developing toxicities (51.0%; p= 0.038), while those with stage III had a lower risk (24.0%; p= 0.052). Of the total, 40.9% (n= 43) of the women had some clinical intervention recorded. Dose reduction was the most common clinical intervention (48.8%, n= 21) with the main cause being the severity of toxicities (57.1%, n= 12). No association was observed between the variables investigated and the occurrence of toxicities grade > 2. Conclusions: the study was able to identify the main toxicities that occured with ovarian cancer patients treated at the institution, and has the potential to assist health professionals in carrying out preventive measures and clinical interventions related to the severity of toxicities that treatment with the investigated regimen can cause.